PERANAN GUEST RELATION OFFICER PADA FRONT OFFICE DEPARTMENT ANGSANA RESORT & SPA BINTAN - Hendrawati, Nanda Lestari; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Angsana Resort & SPA Bintan is part of Banyan Tree Holdings Management. This resort has the most complaints of the guestthat compared by another resort under Banyan Tree Holdings Management. This is caused by a problem ofguest relation officer at front office department. This study was conducted to determine the role of the guest relation officer and the problem face by guest relation officer at the front office department. The research using qualitative method with descriptive approach. Data were obtained from interview with front office manager, assistant front office manager, front office supervisor, guest relation officer and very important guest, as well as direct observation and documentation. Then the data obtained were analyzed using three steps: data reduction, data presentation and conclusion. Result shows that the guest relation officer at this resort work in general to handle the very important guest that need help with the good service as well and do some extra assignment called job description that should be done with the standart operational procedur. This causes the guest relation officer can not work optimally and the resort often received bad comments from the guest. Keywords: Guest Relation Officer, Front Office, Resort